Impact of CO2 activation on the structure, composition, and performance of Sb/C nanohybrid lithium/sodium-ion battery anodes - Liang, Suzhe; Cheng, Ya-Jun; Wang, Xiaoyan; Xu, Zhuijun; Ma, Liujia; Xu, Hewei; Ji, Qing; Zuo, Xiuxia; Müller-Buschbaum, Peter; Xia, Yonggao (2021)
Antimony (Sb) has been regarded as one of the most promising anode materials for both lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) and attracted much attention in recent years. Alleviating the volumetric effect of Sb during charge and discharge processes is the key point to promote Sb-based anodes to practical applications. Carbon dioxide (CO2) activation is applied to improve the rate performance of the Sb/C nanohybrid anodes caused by the limited diffusion of Li/Na ions in excessive carbon components. Based on the reaction between CO2 and carbon, CO2 activation can not only reduce the excess carbon content of the Sb/C nanohybrid but also create abundant mesopores inside the carbon matrix, leading to enhanced rate performance. Additionally, CO2 activation is also a fast and facile method, which is perfectly suitable for the fabrication system we proposed. As a result, after CO2 activation, the average capacity of the Sb/C nanohybrid LIB anode is increased by about 18 times (from 9 mA h g−1 to 160 mA h g−1) at a current density of 3300 mA g−1. Moreover, the application of the CO2-activated Sb/C nanohybrid as a SIB anode is also demonstrated, showing good electrochemical performance.